# -2p+7=6-(7p+5)

## Simple and best practice solution for -2p+7=6-(7p+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -2p+7=6-(7p+5) equation:

Simplifying
-2p + 7 = 6 + -1(7p + 5)

Reorder the terms:
7 + -2p = 6 + -1(7p + 5)

Reorder the terms:
7 + -2p = 6 + -1(5 + 7p)
7 + -2p = 6 + (5 * -1 + 7p * -1)
7 + -2p = 6 + (-5 + -7p)

Combine like terms: 6 + -5 = 1
7 + -2p = 1 + -7p

Solving
7 + -2p = 1 + -7p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7p' to each side of the equation.
7 + -2p + 7p = 1 + -7p + 7p

Combine like terms: -2p + 7p = 5p
7 + 5p = 1 + -7p + 7p

Combine like terms: -7p + 7p = 0
7 + 5p = 1 + 0
7 + 5p = 1

Add '-7' to each side of the equation.
7 + -7 + 5p = 1 + -7

Combine like terms: 7 + -7 = 0
0 + 5p = 1 + -7
5p = 1 + -7

Combine like terms: 1 + -7 = -6
5p = -6

Divide each side by '5'.
p = -1.2

Simplifying
p = -1.2`